Identifying the Anti-inflammatory Effects of Astragalus Polysaccharides in Anti-N-Methyl-D-Aspartate Receptor Encephalitis: Network Pharmacology and Experimental Validation - Lu, Yuling; Wu, Ying; Sun, Lanfeng; Yang, Shengyu; Kuang, Huimin; Li, Rida; Meng, Youshi; Wu, Yuan (Combinatorial Chemistry & High Throughput Screening, 2024)
Background: Astragalus polysaccharides (APS), a group of bioactive compounds obtained from the natural source Astragalus membranaceus (AM), exhibits numerous pharmacological actions in the central nervous system, such as anti-inflammatory, antioxidant, and immunomodulatory properties. Despite the remarkable benefits, the effectiveness of APS in treating anti- N-methyl-D-aspartate receptor (NMDAR) encephalitis and the corresponding mechanism have yet to be fully understood. As such, this study aims to investigate the impact of APS on anti-NMDAR encephalitis and explore the potential molecular network mechanism. Methods: The impact of APS intervention on mice with anti-NMDAR encephalitis was assessed, and the possible molecular network mechanism was investigated utilizing network pharmacology and bioinformatics techniques such as Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG),protein–protein interaction (PPI) network, and molecular docking. Enzymelinked immunosorbent assay (ELISA) was applied to detect the expression of core target proteins. Results: APS significantly ameliorated cognitive impairment and reduced susceptibility to PTZinduced seizures in mice with anti-NMDAR encephalitis, confirming the beneficial effect of APS on anti-NMDAR encephalitis. Seventeen intersecting genes were identified between APS and anti- NMDAR encephalitis. GO and KEGG analyses revealed the characteristics of the intersecting gene networks. STRING interaction in the PPI network was applied to find crucial molecules. The results of molecular docking suggested that APS may regulate interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) as potential targets in anti-NMDAR encephalitis. Furthermore, the levels of IL-1β, IL-6, and TNF-α detected by ELISA in anti-NMDAR encephalitis mice were significantly downregulated in response to the administration of APS. Conclusion: The findings of this study demonstrate the significant role of APS in the treatment of anti-NMDAR encephalitis, as it effectively suppresses inflammatory cytokines. These results suggest that APS has the potential to be considered as a viable herbal medication for the treatment of anti-NMDAR encephalitis.
Keywords: network pharmacology